Asymptotic expansions for distributions of sums of a double sequence of quasilattice random variables - Bikelis, Algimantas; Augutis, Juozas; Padvelskis, Kazimieras (Lietuvos matematikos rinkinys, 2011)
We consider the formal asymptotic expansion of probability distribution of the sums of independent random variables. The approximation was made by using infinitely divisible probability distributions.